Improving Grade IV Students’ Learning on Photosynthesis with Demonstration: Meningkatkan Pemahaman Siswa Kelas IV tentang Fotosintesis Melalui Demonstrasi - Cahyani , Fitri Diah; Rezania , Vanda (Indonesian Journal of Islamic Studies, 2025)
General Background: Education in elementary schools plays a vital role in shaping students’ knowledge, skills, and attitudes, yet many students struggle with understanding complex scientific concepts such as photosynthesis. Specific Background: At SD Islami A-Education Jogosatru Sidoarjo, grade IV students demonstrated low achievement in the photosynthesis topic due to teacher-centered methods and passive learning approaches. Knowledge Gap: Limited studies have explored the application of demonstrative methods to actively engage students in understanding photosynthesis within an Islamic elementary school context. Aim: This study aimed to improve learning achievement and motivation in grade IV students using the demonstration method. Method: A classroom action research (CAR) design was implemented with 29 students over two cycles involving planning, acting, observing, and reflecting. Results: The average score increased from 67.9 in cycle I to 79.82 in cycle II, with 93% of students achieving mastery. Novelty: The study highlights the practical application of demonstration techniques in enhancing comprehension of abstract scientific concepts for young learners in Islamic educational settings. Implications: Findings suggest that active, demonstrative learning strategies can significantly improve student engagement, understanding, and achievement in elementary science education. Highlights: Demonstration method increased comprehension and motivation in grade IV students. Student mastery improved from 45% to 93% across two CAR cycles. Provides a replicable approach for effective science teaching in Islamic elementary schools. Keywords: Demonstration Method, Student Achievement, Photosynthesis, Active Learning, Elementary Science